Livedoid vasculopathy: A multidisciplinary clinical approach to diagnosis and management - Asli Bilgic, MD; Salih Ozcobanoglu, MD; Burcin Cansu Bozca, MD; Erkan Alpsoy, MD, MPhil (Wolters Kluwer, 2021)
Livedoid vasculopathy (LV) is a rare, chronic, and occlusive disease of the veins supplying the upper parts of the skin. The pathogenesis of the disease is not precisely understood, and its attacks are often unpredictable but tend to worsen during the summer. LV affects women more often. This increased risk for LV in women might be related to sex-specific physiological conditions, such as pregnancy, or a higher incidence of LV-associated conditions, such as connective tissue diseases, hypercoagulable states, and venous stasis in women. The typical clinical appearance of LV consists of three main findings: livedo racemose, atrophie blanche, and skin ulcers. The purpose of this comprehensive review was to analyze LV in all aspects and mainly focus on early diagnosis for successful clinical management with a holistic and multidisciplinary approach. A detailed history, dermatological examination, and laboratory testing are essential for a diagnosis of LV. When LV is clinically suspected, a skin biopsy should be taken to confirm the diagnosis. Another critical step is to investigate the underlying associated conditions, such as connective tissue diseases, hypercoagulable states, thrombophilia, and malignancy. Unfortunately, no associated conditions can be detected in approximately 20% of all cases (idiopathic LV) despite all efforts. The diagnosis of the disease is delayed in most patients. Thus, irreversible, permanent scars appear. Early and appropriate treatment reduces pain and prevents the development of scars and other complications. Antiplatelet drugs and anticoagulants can be preferred as the first-line treatments along with general supportive measures. Other therapeutic options might be considered in unresponsive cases. Preference for refractory cases is based on availability, clinical experience, and patient-related factors (comorbidities, age, sex, and compliance). These include anabolic steroids, intravenous immunoglobulin, hyperbaric oxygen therapy, psoralen-ultraviolet A, vasodilators, fibrinolytics, immunomodulators, and immunosuppressives.